Analisis Nilai dan Keterbacaan Kisah Rasulullah sebagai Sumber Bacaan Mata Pelajaran Bahasa Indonesia - Ariffiando, Nady Febri (Jurnal PGSD, 2021)
The use of text with character content Â in learning is one of the efforts to strengthen children's moral kognition which is one of the keys to ordering characters. This study aimed to analyze the character values contained in the story of Rasulullah and test the readability of the story. The results of the value analysis by were validated by value education experts, language education experts in elementary schools and hadis experts. Researchers conducted a readability test using Raygor and fry graph. The results show that there are five stories that contained the main values of social care and the accompaniment values of patience, empathy and generosity. The readability test results show that the five stories are suitable for reading by children aged 1o to 12 years. From these results, the story of the Prophet is right for use in literary learning with the aim of instilling character.